Effect of vitamin B(6) deficiency on antioxidative status in rats with exercise-induced oxidative stress - Choi, Eun-Young (The Korean Nutrition Society and The Korean Society of Community Nutrition, 2009)
This study investigated the effect of vitamin B(6) deficiency on antioxidant enzyme activities and lipid profile in rats with exercise-induced oxidative stress. Forty eight rats were fed either a vitamin B(6) deficient diet (B6-) or a control diet (control) for 4 weeks and then subdivided into 3 groups: pre-exercise (PreE); post-exercise (PostE); recess after exercise (recessE). Compared to those of control group, plasma catalase and hepatic cytosol superoxide dismutase (SOD, EC 1.15.1.1) activities of B6- group were lower regardless of exercise. The ratio of reduced glutathione/oxidized glutathione (GSH/GSSG) of B6- group was lower in PreE and there was no difference between PostE and recessE. The level of malondialdehyde (MDA) of B6- was significantly higher in PreE and PostE. High-density lipoprotein-cholesterol (HDL-C) level of B6- group was lower regardless of exercise. Atherosclerotic index of B6- group was higher in PreE and there was no difference between PostE and recessE. It is suggested that a reduction in antioxidative status caused by vitamin B(6) deficiency may be aggravated under exercise-induced oxidative stress.